A polgári eljárások egyszerűsítése az Európai Unióban, különös tekintettel a kis pertárgyértékű ügyek szabályozására - Nyilas, Anna (Debreceni Jogi Műhely, 2006)
Introduced to reduce obstacles to the free movement of goods and persons, judicial cooperation in civil matters has become part and parcel of the new European area of justice. Creation of this area is meant to simplify the existing legal environment and to reinforce citizens’ feeling of being part of a common entity. The Conclusions of the Tampere European Council state in this respect that “in a genuine European Area of Justice individuals and businesses should not be prevented or discouraged from exercising their rights by the incompatibility or complexity of legal or administrative systems in the Member States.” At present, the judicial cooperation in civil procedures is based on the Hague Programme, adopted by the 2004 Europen Council in Bruxelles.The Hague Programme requires that the Commission should translate the Hague objectives into concrete measures. To this end, the Annex to the Communication from the Commission to the Council and the. European Parliament on the Hague Programme, consists of an Action Plan listing the main actions and measures to be taken over the next five years, including a specific set of deadlines for their presentation to the Council and the European Parliament. The chapter dealing with this area is named „Strengthening justice”, and it includes amongst others the following tasks: Specific Programme on Judicial Cooperation in Civil and Commercial Matters (2007) Support by the Union to networks of judicial organisations and institutions (continuous) Creating a „European Judicial culture” Evaluation of quality of justice (Communication - 2006) Creation, from the existing structures, of an effective European training network for judicial authorities for both civil and criminal matters (2007) The European Union has set itself the objective of maintaining and developing the European Union as an area of freedom, security and justice in which the free movement of persons is ensured. For the gradual establishment of such an area, the Community is to adopt, among others, the measures relating to judicial cooperation in civil matters needed for the proper functioning of the internal market. The Community has among other measures already adopted Council Regulation (EC) No 1348/2000 of 29 May 2000, on the service in the Member States of judicial and extrajudicial documents in civil or commercial matters; Council Decision 2001/470/EC of 28 May 2001, establishing a European Judicial Network in civil and commercial matters; Council Regulation (EC) No 44/2001 of 22 December 2000 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters; Regulation (EC) No 805/2004 of the European Parliament and of the Council of 21 April 2004, creating a European Enforcement Order for uncontested claims; Council Directive 2002/8/EC, of 27 January 2003, to improve access to justice in cross-border disputes by establishing minimum common rules relating to legal aid for such disputes; Council Regulation (EC) 2201/2003, of 27 November 2003, concerning jurisdiction and the recognition and enforcement of judgments in matrimonial matters and the matters of parental responsibility, repealing Regulation (EC) 1347/2000; Regulation (EC) No 805/2004, of the European Parliament and of the Council of 21 April 2004, creating a European Enforcement Order for uncontested claims; Proposal for a regulation of the European Parliament and of the Council creating a European order for payment procedure; Proposal for a regulation of the European Parliament and of the Council establishing a European Small Claims Procedure. The disproportionate cost of litigation for small claims has led many Member States to provide simplified procedures for claims of small value which are intended to provide access to justice at a lower cost, thus influencing one of the three factors that determine the rationales in dispute resolution. The details of these procedures have been investigated and documented in detail in studies prepared for the Commission. The evidence from these reports suggests that the costs and timescale associated with the domestic simplified measures, and thus their use and utility to claimants, varies widely. A 1995 study for the Commission found evidence of how costs of cross-border claims were significant compared to the size of most potential claims, and that these costs varied substantially between Member States. The total costs of pursuing a cross-border claim with a value of € 2.000 was found to vary, depending on the combination of Member States, from € 980 to € 6.600, with an average quoted figure of € 2.489 for a proceeding at the plaintiff’s residence. The study also showed that due to different and conflicting costing rules part of the costs have to be paid even by successful plaintiffs. On 20 December 2002, the Commission adopted a Green Paper on a European order for payment procedure and on measures to simplify and speed up small claims litigation. The Green Paper launched a consultation on measures concerning the simplification and the speeding up of small claims litigation. The European Small Claims Procedure is meant to simplify and speed up litigation concerning small claims, whilst reducing costs, by offering an optional tool in addition to the possibilities existing under the laws of the Member States. This Regulation should also make it simpler to obtain the recognition and enforcement of a judgment given in a European Small Claims Procedure in another Member State, including judgements which were initially of a purely domestic nature. In order to facilitate the introduction of the procedure, the claimant should commence the European Small Claims Procedure by completing a claim form and lodging it at the competent court or tribunal. In order to reduce costs and delays, documents should be served on the parties by registered letter with acknowledgment of receipt, or by any simpler means such as simple letter, fax or email. The procedure should be a written procedure, unless an oral hearing is considered necessary by the court. The parties should not be obliged to be represented by a lawyer. The court should be given the possibility to hold a hearing through an audio, video or email conference. It should also be given the possibility to determine the means of proof and the extent of the taking of evidence according to its discretion and admit the taking of evidence through telephone, written statements of witnesses, and audio, video or email conferences. The court should respect the principle of an adversarial process. In order to speed up the resolution of disputes, the judgment should be rendered within six months following the registration of the claim. In order to speed up the recovery of small claims, the judgment should be immediately enforceable notwithstanding any possible appeal and without the condition of the provision of a security. In order to reduce costs, when the unsuccessful party is a natural person and is not represented by a lawyer or another legal professional, he should not be obliged to reimburse the fees of a lawyer or another legal professional of the other party. In order to facilitate recognition and enforcement, a judgment given in a Member State in a European Small Claims Procedure should be recognised and enforceable in another Member State without the need for a declaration of enforceability and without any possibility of opposing its recognition. Since the objectives of the action to be taken namely the establishment of a procedure to simplify and speed up litigation concerning small claims, and reduce costs, cannot be sufficiently achieved by the Member States and can therefore be better achieved at Community level, the Community may adopt measures in accordance with the principle of subsidiarity as set out in Article 5 of the Treaty. In accordance with the principle of proportionality as set out in that Article this Regulation does not go beyond what is necessary to achieve those objectives. The European Council underlines the need further to enhance work on the creation of a Europe for citizens and the essential role that the setting up of a European Area for Justice will play in thisrespect. A number of measures have already been carried out. Further efforts should be made to facilitate access to justice and judicial cooperation as well as the full employment of mutual recognition. It is of particular importance that borders between countries in Europe no longer constitute an obstacle to the settlement of civil law matters or to the bringing of court proceedings and the enforcement of decisions in civil matters.